LANGUAGE CHOICE USED BY CHINESE FAMILY IN LANGSA - Yusmawati Yusmawati; Cut Intan Lestari; Nurul Hidayah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
The research aims at identifying the language choice used by Chinese family in Langsa, the phenomenon that has long been seen in Chinese families: having tendency to choose Indonesian as the second language in their families even though they live in the Aceh region. This phenomenon is not only seen in the town but also in urban areas. The emergence of language selection is caused by the occurrence of language, social condition, and cultural tradition. The interesting thing to look at and study in connection with this phenomenon is that members in the family are from the Chinese ethnic group and speakers of native Chinese but the language used to communicate with the community in the chosen environment is Indonesian. The focus of this research is to analyze language selection Indonesia in a Chinese family in Langsa. The research is executed by means of descriptive qualitative method supported by the technique of interview to get deep information about the language choice.